Sharī‘a Scripts: A Historical Anthropology By Brinkley Messick (New York: Columbia University Press, 2018. 534 pages.) (American Journal of Islam and Society, 2019)
While the Yemen seems to be stumbling from one disaster into the next, it is good to see how some of the best experts in Yemeni studies continue their work in ways that will be useful in the country’s future. The present volume is not only bound to become recognized soon as the magnum opus by Brinkley Messick, professor of  anthropology and Middle Eastern, South Asian and African studies at Columbia University and one of the world’s leading experts in Yemeni studies today. More importantly still, Sharī‘a Scripts features all the qualities required for a true academic milestone in Yemen-related scholarship for decades to come, with potential ramifications for the historical and legal anthropology of the Middle East at large. This volume is based on half a lifetime of analytical and comparative studies that began during the author’s first fieldwork period in the central and southern highlands of northern Yemen during the 1970s. Messick meticulously examines the structures of jurisprudence (the “library” in his terms) with the methodologies and techniques of textual scholarship, while relating it to the “archive” of records concerning everyday interactions in legal life as embedded within the practical interplay of fields between orality and scriptural statements.To download full review, click on PDF.